Pendapatan dan Kerentanan Petani Kopi Robusta di Sekitar Kawasan Taman Nasional Bukit Barisan Selatan (Jurnal Agribisnis Indonesia, 2023)
Coffee, the prominent plantation commodity in Indonesia, exhibits significant potential due to its substantial consumption and production trends. Alongside tea and spices (HS code 09), coffee accounted for 41.5 percent of Indonesia's total agricultural exports between 2016 and 2020. South Sumatra, Lampung, Aceh, and East Java serve as the primary coffee production regions in the country. However, this burgeoning industry has led to adverse effects on land conversion, particularly in Lampung province, where 60 percent of the forest area in Bukit Barisan Selatan National Park (TNBBS) has been converted for agricultural purposes, with 73 percent being utilized for Robusta coffee fields. Despite the promising outlook, the Covid-19 pandemic introduced new challenges to the coffee farming sector. This study aims to analyze and compare the income levels and vulnerability of coffee farming families inside and outside the TNBBS area during the pandemic. Primary data were collected through direct interviews, utilizing a non-probability sampling quota sampling method. The analysis includes farm income assessment with evaluation of poverty levels among farmer households and livelihood vulnerability index. Results indicate that coffee farmers outside the TNBBS area experience higher income and profits compared to their counterparts within TNBBS. Additionally, the poverty rate is higher for farmers within the TNBBS area. Vulnerability analysis reveals a medium-scale vulnerability level for farming families in both regions, emphasizing the necessity for targeted support to enhance their resilience.